Integrated profiling uncovers prognostic, immunological, and pharmacogenomic features of ferroptosis in triple-negative breast cancer - Fang, Kun; Xu, Zhengjie; Jiang, Suxiao; Yan, Changsheng; Tang, Desheng; Huang, Yan (Frontiers in Immunology, 2022)
Objective: Ferroptosis is an iron-dependent type of regulated cell death triggered by the toxic buildup of lipid peroxides on cell membranes. Nonetheless, the implication of ferroptosis in triple‐negative breast cancer (TNBC) that is the most aggressive subtype of breast carcinoma remains unexplored. Methods: Three TNBC cohorts: TCGA-TNBC, GSE58812, and METABRIC were adopted. Consensus molecular subtyping on prognostic ferroptosis-related genes was implemented across TNBC. Ferroptosis classification-relevant genes were selected through WGNCA, and a ferroptosis-relevant scoring system was proposed through LASSO approach. Prognostic and immunological traits, transcriptional and post-transcriptional modulation, therapeutic response, and prediction of potential small molecule agents were conducted, respectively. Results: Three disparate ferroptosis patterns were identified across TNBC, with its own prognostic and immunological traits in each pattern. The ferroptosis-relevant scoring system was proposed, with poorer overall survival in high-risk patients. This risk score was strongly linked to transcriptional and post-transcriptional mechanisms. High-risk group had a higher response to anti-PD-1 blockade or sunitinib, with higher sensitivity to cisplatin for low-risk group. High relationships of risk score with immunological features were observed across pan-cancer. Two CTRP-derived agents (SNX-2112, brefeldin A) as well as PRISM-derived agents (MEK162, PD-0325901, PD-318088, Ro-4987655, SAR131675) were predicted aiming at high-risk patients. Conclusion: Altogether, our findings unveil prognostic, immunological and pharmacogenomic features of ferroptosis in TNBC, highlighting the potential clinical utility of ferroptosis in TNBC therapy.